Direct Oral Anticoagulants in Cirrhotic Patients: Current Evidence and Clinical Observations. (8th January 2019) - Elhosseiny, Sherif; Al Moussawi, Hassan; Chalhoub, Jean M.; Lafferty, James; Deeb, Liliane
Abstract : The introduction of Direct Oral Anticoagulants (DOACs) to the pharmaceutical market provided patients and clinicians with novel convenient and safe options of anticoagulation. The use of this class of medications is currently limited to venous thromboembolic therapy and prophylaxis, in addition to stroke prophylaxis in patients with nonvalvular atrial fibrillation. Despite their altered hemostasis, patients with cirrhosis are thought to be in a procoagulant state and thus prone to thrombus formation. Patients with cirrhosis might benefit from the convenience of DOACs; however, the medical literature includes limited data on the efficacy and safety of DOACs in this special patient population. The aim of this review is to summarize the current evidence for anticoagulation options in patients with cirrhosis and their safety profile.